Eager Visitor, Reluctant Host: The Anthropologist as Stranger - Manyoni, Joseph R. (Anthropologica, 2022)
The role of the anthropologist in field research is by its nature ambiguous, whether we study an alien culture or an unfamiliar subculture in our own society. In an alien culture, the anthropologist is a stranger par excellence, an outsider in both the physical and cultural sense. This paper reevaluates the fieldwork situation as encountered by initiate ethnographers in alien cultures, and analyzes the ethnographer’s transient position in terms of Simmel’s seminal notion of "the stranger." The paper argues that the anthropologist’s stranger/host interpersonal relationships with members of the research community constitute a crucial datum with serious implications for the acquisition and analysis of research data. As presented in ethnographic accounts, the field situation largely reflects the influence of psychosocial factors, interpersonal relationships, and cognitive bias due to the adaptive problems of being a stranger. However, insufficient consideration has been taken of these factors in ethnographic reports. Methodologically, this paper utilizes the growing volume of ex post facto ethnographic reports to question the validity and reliability of some research conclusions.